REVOLUTION OR DIVERSITY? AESTHETIC AND POLITICAL MANIFESTATIONS OF CLASS IN THREE SWEDISH RADICAL PICTUREBOOKS FROM THE 2000S AND 2010S - Hermansson, Kristina (The Nordic Journal of Aesthetics, 2020)
This article explores manifestations of class from a combined aesthetical and political point of view, focusing on a selection of Swedish children’s picture books from 2009 to 2018, in which class differences are made prominent. In this sense, they can be regarded as radical. This study examines how political aspects are intertwined with literary, visual, and multimodal means. The main purpose is to examine how the political and aesthetical merge in the manifestations of class. The publishing of radical picture books during the 2000s and 2010s coincided with a rise of norm-criti-cal discourse, including a strong emphasis on diversity rather than on social transformation. The books, I argue, do not depict radical change on a collective level, but uses various aesthetic means in their manifestations of class and inequality. Theoretically, the anal-ysis mainly draws on Pierre Bourdieu’s theory of capital (1984), and Beverley Skeggs’s (1997) reasoning on class by adding the con-cept of respectability, as well as picturebook theory, and scholarly writing on radical picturebooks.